2023
DOI: 10.3389/fneur.2023.1158555
|View full text |Cite
|
Sign up to set email alerts
|

OEDL: an optimized ensemble deep learning method for the prediction of acute ischemic stroke prognoses using union features

Abstract: BackgroundEarly stroke prognosis assessments are critical for decision-making regarding therapeutic intervention. We introduced the concepts of data combination, method integration, and algorithm parallelization, aiming to build an integrated deep learning model based on a combination of clinical and radiomics features and analyze its application value in prognosis prediction.MethodsThe research steps in this study include data source and feature extraction, data processing and feature fusion, model building a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Notably, 11 of these studies performed a comparation between models using only clinical features and models incorporating radiomics features. While 4 of these studies ( 41 43 , 46 ) did not observe a significant difference in predictive performance, the remaining 7 ( 13 , 38 , 39 , 44 , 47 49 ) demonstrated that the inclusion of radiomics significantly improved the predictive ability for AIS prognosis. Moreover, among these 7 studies, 3 ( 38 , 39 , 44 ) directly compared the performance of the radiomics model with the clinical model, and all found that the radiomics model was superior.…”
Section: Resultsmentioning
confidence: 96%
“…Notably, 11 of these studies performed a comparation between models using only clinical features and models incorporating radiomics features. While 4 of these studies ( 41 43 , 46 ) did not observe a significant difference in predictive performance, the remaining 7 ( 13 , 38 , 39 , 44 , 47 49 ) demonstrated that the inclusion of radiomics significantly improved the predictive ability for AIS prognosis. Moreover, among these 7 studies, 3 ( 38 , 39 , 44 ) directly compared the performance of the radiomics model with the clinical model, and all found that the radiomics model was superior.…”
Section: Resultsmentioning
confidence: 96%
“…The OEDL method achieved a Macro-AUC of 97.89% and ACC of 95.74%. The SMOTEENN-based mixed sampling method exhibited the best classification performance, with Macro-AUC, ACC, Macro-R, Macro-P, and Macro-F1 reaching 97.89, 95.74, 94.75, 94.03, and 94.35%, respectively ( 93 ).…”
Section: Progress In Predicting the Rehabilitation Of Ischemic Stroke...mentioning
confidence: 99%